Smart fertilizer subsidies in Sub-Saharan Africa: New wine or just new bottles? - Minot, Nick (2009)
Presentation by Nick Minot at the IFPRI Panel Discussion, Smart Input Subsidies and Sustainable Agricultural Development, Washington DC, July 24, 2009.